Lights out! : living in 24-hour darkness - Callery, Sean. (Mankato, Minn. : Capstone Press, 2008)
Describes the science behind an arctic winter, including its effects on daily life for people and wildlife.
Twilight world -- Don't move! -- Surviving in the freezer -- Chiller killer -- Make sense of hunting -- A good hiding -- Snow houses -- Watch the crack -- Slide show -- Welcome back! -- Snow-blind -- Have an ice trip -- Melting world.
Includes bibliographical references (p. 31) and index.
5.3
3-6
Keywords: Inuit -- Arctic regions -- Social life and customs -- Juvenile literature; Animals -- Arctic regions -- Juvenile literature; Cold adaptation -- Arctic regions -- Juvenile literature; Arctic regions -- Climate -- Juvenile literature; Arctic regions -- Social life and customs -- Juvenile literature; Inuit; Animals; Arctic regions; Cold adaptation; Inuit; Animals; Arctic regions; Cold adaptation